Chessbot: a chemical safety and security telegram chatbot in Bahasa Malaysia - Mohammad, Nurul Farahain; Zakaria, Siti Fatimah; Hamzah, Nurasyikin; Aminudin, Nurul Iman; Ismail, Mohamad Wafiuddin (Unit Penerbitan UiTM Cawangan Pulau Pinan, 2022)
Laboratory exercises are an acknowledged way to stimulate students learning subject matter, not the least in the subject of chemistry, where the craft of laboratory work also is essential for future studies and careers in chemistry. Key learning objectives are therefore that students develop their ability to plan, implement, interpret, and report experiments and observations as well as their ability to handle chemicals and equipment. Having acquired good chemical safety habits early, students are better prepared when they move on to more advanced courses. However, teachers and students are exposed to chemical hazards and incidents especially related to chemical handling. Due to the health impacts caused by these incidents, we aimed to provide chatbot with all the information related to chemical handling and safety. This chatbot will provide quick access to the information and background (hazard and safety) of the chemicals that will be used. The chatbot is developed in Python using PyTelegrambotAPI with /nama and /cas as triggering commands, and the search function is conducted using Pandas. At the moment, this chatbot is deployed on PythonAnywhere and accessible for end-users via Telegram at @chemicalsafetybot. Using CheSSBot, users can check chemical safety and security information in Bahasa Malaysia. Simply launch CheSSBot in Telegram. Next, users may check chemical information based on name by typing /nama followed by chemical name. Alternatively, users may also check based on CAS number by typing /cas. Once sent, the chatbot will return the type of chemical (jenis bahan kimia), related GHS codes (amaran bahaya), storage method (kaedah penyimpanan), how to dispose of the chemical (cara pelupusan) and a link to PubChem for further info (info lanjut). We chose to develop this chatbot in Telegram so that users may retrieve the information from Android devices, iPhones or Telegram desktop chatbot. With this information being easily accessible to users, it is hoped that chemicals will be stored and disposed of in a much safer way.